Property rights, standards of living, and economic growth: Western Canadian Cree - Ann M. Carlos; Frank Lewis (Queen's University, Department of Economics, 2010)
The Great Divergence in standards of living for populations around the world occurred in the late 18th century. Prior to that date evidence suggests that real wages of most Europeans, many living in China and India were similar. Some a little higher and some a little lower but with a low dispersion. By the middle of the 19th century, a divergence had occurred with western Europe pulling away from other groups. Little is known about the standards of living of the aboriginal peoples of North America many of whom were primarily hunter/gatherer's at the end of the 18th century. Based on comparisons of expenditure, we show that the standard of living of aboriginal people in 1740 was similar to that of wage workers in London. However, within the next century, there would be a great divergence. This paper explores the ways in which hunter-gatherer lifeways and the concomitant property rights structures reduced the likelihood that native economy could experience modern rates of economic growth. Native society and property rights structures which provided a relatively high standard of living in the mid eighteenth century and for part of the nineteenth was unable to provide avenues for further development.
Keywords: I31; N31; N51; 330; native americans; living standards; property rights; Soziale Lage; Einkommen; Eigentumsrecht; Lebensstandard; Indigene Völker; Wirtschaftswachstum; Sozialgeschichte; Welt